Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw untuk Meningkatkan Hasil Belajar Siswa Materi Sistem Reproduksi pada Hewan di Kelas 9 Smp - Pramudita Wardani, Putri; Waris, Waris; Sugianto, Ferdy (JOEAI (Journal of Education and Instruction), 2025)
This study aims to enhance student learning outcomes by implementing the Jigsaw cooperative learning model on the animal reproductive system for ninth-grade students at SMP Kartika IV-6 Ambulu. The research method employed was Classroom Action Research (CAR), which consisted of two cycles and involved a collaborative process among students in study groups. Each group member was responsible for studying and presenting different sections of the material to their peers. The results showed a significant increase in students' conceptual understanding and academic performance after implementing the Jigsaw model. Furthermore, student learning activities became more active, collaboration among students increased, and the classroom atmosphere became more conducive to meaningful learning. In conclusion, the Jigsaw cooperative learning model has proven effective in improving student learning outcomes and fostering social and communication skills.   Keywords: Student Learning Outcomes, Social Skills, Cooperative Learning Model, Meaningful Learning, Animal Reproductive System, Jigsaw